Striving Toward Openness: But What Do We Really Mean? - Rolfe, Vivien (International Review of Research in Open and Distributed Learning, 2017)
The global open education movement is striving toward openness as a feature of academic policy and practice, but evidence shows that these ambitions are far from mainstream, and levels of awareness in institutions is often disappointingly low. Those advocating for open education are seeking to widen engagement, but how targeted and persuasive are their messages? The aim of this research is to explore the voices often unheard, those of the teachers and professional service staff with whom we are engaging. This research presents a series of interviews with those involved in open education at De Montfort University in the UK, with the aim of gaining a better perspective of what openness means to them. The interviews were analysed through an interpretive lens allowing each individual to create their own story and reflect their own personal view of openness. The results of this study are that in this university, openness is represented by five elements – staff pedagogy and practice, benefits to learners, accessibility and access to content, institutional structures, and values and culture. This work shows the importance of adopting critical approaches to gain a deeper understanding of the philosophical and pedagogic stances within institutions.  By giving a voice to all those involved we will be able to develop appropriate and more persuasive arguments to widen our sphere of influence as a community of open educators.